Pentingnya Peran Orang Tua Dalam Pembentukan Karakter Anak Sekolah Dasar - hidayati, alvina; Pritasari, Ade Cyntia (Universitas Negeri Surabaya, 2025)
This study aims to evaluate the significant contribution parents make to their children's character development in elementary school. Children's character development at this age is significantly influenced by their home environment, particularly through parent interactions and parenting approaches. Reviewing pertinent studies on the connection between children's character development and parental roles was the study methodology employed. The findings of the study demonstrate that parents can inculcate virtues like discipline, responsibility, honesty, and empathy in their children by actively educating them through monitoring, effective communication, or positive behavior. Furthermore, it has been demonstrated that parental involvement in educational activities at home and at school can improve kids' social skills, such as their capacity for peer interaction and cooperation. In conclusion, as parents have a significant and undeniable influence on the character development of elementary school pupils, further active parental involvement is needed to support children's better character development in the future.